The role of vitamin D in the development of anemia of inflammation in young children with acute inflammatory bacterial diseases of the respiratory system - Pohribna, A. O.; Погрібна, Анастасія Олександрівна (My University, 2020)
In the last decade, the concept of the polymodal function of vitamin D in the children's body has expanded significantly. In particular, it became known about the effect of vitamin D on the synthesis of the antimicrobial peptide hepcidin, a marker of iron metabolism, which implements a protective function by reducing the bioavailability of iron, necessary for the growth of bacterial pathogens. We can assume an interconnection between vitamin D content in the blood serum and the risk of anemia of inflammation, the leading mechanism of which includes the induction of hepcidin by proinflammatory cytokines.
Keywords: vitamin D; children; hepcidin